Is double-crossed retrograde elastic stable intramedullary nailing an alternative method for the treatment of diaphyseal fractures in the adult humerus? - Hsuan-Hsiao Ma; Chao-Ching Chiang; Yu-Ping Su; Kun-Hui Chen (Journal of Orthopaedics and Traumatology, 2022)
Abstract Background The aim of this study was to compare two techniques for the surgical treatment of diaphyseal fractures in the adult humerus: double-crossed retrograde elastic stable intramedullary nailing (DCR-ESIN) and limited-contact dynamic compression plate (LC-DCP). Methods This was a retrospective study conducted at a single hospital. We included 122 patients with diaphyseal fractures of the humerus who had received DCR-ESIN or LC-DCP from January 2011 to January 2017. We compared union rates, union times, disabilities of the arm, shoulder, and hand (DASH) scores at the postoperative 1-year follow-up, and complications between the two groups. Results Plating management was performed in 63 patients, while DCR-ESIN was performed in 59 patients. The union rate was higher in the DCR-ESIN group than in the LC-DCP group (100% vs. 90.5%; p = 0.052). The union time was shorter in the DCR-ESIN group than in the LC-DCP group (12.0 weeks vs. 14.8 weeks; p < 0.001). The intraoperative blood loss and operative time were less in the DCR-ESIN group than in the LC-DCP group (76.4 min vs. 129.5 min; p < 0.001; 60.9 ml vs. 244.8 ml; p < 0.001, respectively). The DCR-ESIN had superior results for the rate of overall complications (p = 0.006). At the 1-year follow-up, the DCR-ESIN group had better DASH scores than the LC-DCP group (p = 0.014). Conclusions The DCR-ESIN technique, used to treat diaphyseal fractures of the humerus, has shorter operative times, less intra-operative blood loss, shorter union times, and better functional outcomes at 1-year follow-up than the LC-DCP technique. DCR-ESIN may be an alternative method for the surgical treatment of diaphyseal humeral fractures in adults.